Effects of In-Season Explosive Strength Training on Maximal Leg Strength, Jumping, Sprinting, and Intermittent Aerobic Performance in Male Handball Athletes - Hermassi, Souhail; Chelly, Mohamed Souhaiel; Fieseler, Georg; Bartels, Thomas; Schulze, Stephan; Delank, Karl-Stefan; Shephard, Roy J.; Schwesig, René (Sportverletzung · Sportschaden, 2017)
Background Team handball is an intense ball sport with specific requirements on technical skills, tactical understanding, and physical performance. The ability of handball players to develop explosive efforts (e. g. sprinting, jumping, changing direction) is crucial to success.Objective The purpose of this pilot study was to examine the effects of an in-season high-intensity strength training program on the physical performance of elite handball players.Materials and methods Twenty-two handball players (a single national-level Tunisian team) were randomly assigned to a control group (CG; n = 10) or a training group (TG; n = 12). At the beginning of the pilot study, all subjects performed a battery of motor tests: one repetition maximum (1-RM) half-squat test, a repeated sprint test [6 × (2 × 15 m) shuttle sprints], squat jumps, counter movement jumps (CMJ), and the Yo-Yo intermittent recovery test level 1. The TG additionally performed a maximal leg strength program twice a week for 10 weeks immediately before engaging in regular handball training. Each strength training session included half-squat exercises to strengthen the lower limbs (80 – 95 % of 1-RM, 1 – 3 repetitions, 3 – 6 sets, 3 – 4 min rest between sets). The control group underwent no additional strength training. The motor test battery was repeated at the end of the study interventions.Results In the TG, 3 parameters (maximal strength of lower limb: η² = 0.74; CMJ: η² = 0.70, and RSA best time: η² = 0.25) showed significant improvements, with large effect sizes (e. g. CMJ: d = 3.77). A reduction in performance for these same 3 parameters was observed in the CG (d = -0.24).Conclusions The results support our hypothesis that additional strength training twice a week enhances the maximal strength of the lower limbs and jumping or repeated sprinting performance. There was no evidence of shuttle sprints ahead of regular training compromising players’ speed and endurance capacities.
Keywords: team handball; muscular strength; jumping performance; RSA test